Insidensi dan Identifikasi Molekuler Papaya ringspot virus pada Pepaya di Jawa - Farida, Naimatul; Damayanti, Tri Asmira; Efendi, Darda; Hidayat, Sri Hendrastuti (Jurnal Fitopatologi Indonesia, 2022)
Incidence and Molecular-Based Identification of Papaya ringspot virus Infecting Papaya in Java Infection of Papaya ringspot virus (PRSV) in Indonesia was first reported in papaya in Nangroe Aceh Darussalam. Since then, ring spot disease in papaya has spread to several areas in Java, Sumatra, Bali, and West Nusa Tenggara. This study was conducted to confirm the presence of PRSV in several papaya growing areas in Java and to characterize its molecular identity. Double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) method using PRSV-specific antiserum was carried out to detect PRSV infection from field samples. The incidence of ring spot disease based on DAS-ELISA in Bogor, Purworejo, Kebumen, and Bantul was 59.1%, 51.4%, 84.2%, and 96.2%, respectively. Further identification was done by reverse transcription-polymerase chain reaction using specific primers (PRSV326/PRSV800), followed by DNA sequencing. DNA fragment of 475 bp was successfully amplified from field samples and nucleotide analysis showed that all samples confirmed as PRSV with homology between isolates ranging from 95.4% to 99.4%. Phylogenetic analysis showed that PRSV isolates from Java belongs to the same group with PRSV-P isolate from Thailand.